Book Review - Ashari Cahyo Edi (PCD Journal, 2021)
In Participation Without Democracy, Garry Rodan argues that as a response to the dynamics and contradiction inherent in the capitalist development, the regime—representing the dominant coalition of interest, the ruling/dominant political elites—‘invent’ ways to contain conflicts with societal entities (i.e., opposition parties, civil societies, labor unions) in a way so that such conflicts do not yield politically harmful impacts. This argument is based on two propositions. First, the development of capitalism has caused inequality to deepen. Both the ruling political-economy elites and the marginal groups found this inherent inequality and disruption in capitalism created political challenges, which, as a consequence, demand mitigation strategies. Second, the established coalition of interest's tactics handle political dissents towards the regimes move beyond the binary scenarios, not just merely opening political participation or applying coercion means such as crackdown and arrest. Instead, while the elites design the participation and representation institutions as a response to domesticating dissents and conflicts, the marginal groups also respond to those channels beyond being co-opted or merely refuse to join it. Opposition parties, radical NGOs, marginal groups seek to utilize the institutions for their transformative agenda. In short, both the ruling elites and the marginal groups have been engaged in the participating institutions with different goals in mind.